Meta-análise e análises de componentes principais do uso de tortas de oleaginosas na dieta de vacas leiteiras - Santos, Girlene Cordeiro de Lima (2021)
With the increase in the global population, the demand for dairy protein sources has been increasing. Dairy farming is a source of income for small and large producers. The milk production scenario has become increasingly dynamic to meet current consumer demands. However, there is a need to provide a balanced diet to meet the animal's nutritional requirements. Feeding represents 70% of livestock production costs. The use of co-products is a practice capable of reducing these costs, since it partially replaces components of traditional diets, such as soybean, a protein food, and corn, an energy concentrate. However, for the success of this type of management, it is necessary to know the efficiency of the animal in coproduct diets. As an alternative, the cakes, resulting from the process of oil extraction from oilseeds grains consist of foods rich in lipids and protein. The different types of cakes offer the most varied chemical and bromatological compositions, which confer different responses of the animal. In this study, the objective was to carry out a systematic review and a meta-analysis to evaluate the effects of cakes on intake and apparent digestibility of dry matter (DAMS), production and composition of milk from lactating dairy cows. The survey of outcomes for the systematic review and acquisition of meta-analysis data was conducted in the databases Science.gov, Scopus Preview, PubMed, Web of Science, SciELO, Science Direct, CAPES Journal Portal, WorldWideScience.org, Google Scholar, Academia.edu, Portal de Busca Integrada and EpringerLink, considering articles published between 2009 and 2019. The data set used in meta-analysis came from 51 papers published between 2009-2019, which resulted in 119 studies with 18 types of cakes evaluated in 1,350 cows. The data dispersions of cow attributes and diet characteristics were analyzed using BoxPlots. The effect size of each study was measured by the standardized mean difference and the fixed and randomized effect models were adjusted. Heterogeneity and publication views tests were applied. Principal component analysis was used to explain the heterogeneity of results and identify the contribution of each diet fraction, cake type and content in the responses of the analyzed variables. Cows fed with cakes increased dry matter intake (IMS) by 0.366 kg d-1 (P <0.001) and IMS as a function of live weight of the animal by 0.103% (P<0.000) in relation to the diet without cake. The milk protein concentration reduced by 0.050% (P<0.010). The fiber content in neutral detergent (FDN) (26 to 50%) and ethereal extract EE (3% to 7%) of cake diets did not affect DAMS. The effect of inserting the cake in milk production also depended on the proportion of cake, FDN and IMS concentrations. cakes at levels of 10 to 30% can replace the corn/soybean in the diet without affecting milk production, the production of milk components (fat, protein and lactose) and the concentrations (fat and lactose) of milk, but can reduce the concentration of milk protein.